Computer simulations of the dynamic properties of methane in a model silica gel - Patsahan, T.; Trokhymchuk, A.; Holovko, M. (Condensed Matter Physics, 2003)
Molecular dynamics (MD) simulations are reported for a Lennard-Jones fluid adsorbed into a model silica gel to study the dynamic properties of the adsorbed methane molecules. The mean-square displacement and velocity autocorrelation function of the adsorbed molecules are calculated for a set of supercritical temperatures at low (gas-like) and high (liquid-like) fluid densities and compared with the same data for a bulk fluid. The evaluated radial distribution functions illustrate the formation of a contact layer on the pore surface that is consistent with the decrease in the mobility of the adsorbed molecules in a porous environment. The calculated self-diffusion coefficient indicates a good quantitative agreement with the measured data for methane confined to the silica gel. Було здійснено комп’ютерне моделювання методом молекулярної динаміки (МД) для Ленарда-Джонсівського флюїда адсорбованого в модельному силікагелі. Обчислено функції середньо-квадратичного відхилення координат та автокореляційні функції швидкостей частинок флюїда при малих та великих густинах. Пораховані радіальні функції розподілу ілюструють явище формування контактного шару на поверхні пор, яке приводить до зменшення рухливості молекул, адсорбованих в пористому середовищі. Отримані значення для коефіцієнта самодифузії добре узгоджуються із експериментальними даними для метану, адсорбованому в силікагелі.